2017
DOI: 10.1007/s00784-017-2205-0
|View full text |Cite
|
Sign up to set email alerts
|

Short implants versus bone grafting and standard-length implants placement: a systematic review

Abstract: Objectives The aim of this study was to conduct a systematic review to compare the survival rates between short implants (length < 10 mm) versus standard-length implants (≥ 10 mm) inserted in grafted bone. As secondary outcomes, marginal bone loss and survival rates of the implant supported prostheses were also analysed. Materials and methods Randomised controlled trials (RCT) that compared both techniques were searched on three electronic databases till June 2016, a manual search was performed on the bibliogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 32 publications
5
33
0
2
Order By: Relevance
“…The current results are comparable with previous systematic reviews comparing short implants to longer implants and showed no significant difference of marginal bone loss . Crown height space, splinting of crowns, occlusal loading, and implant design that can influence the marginal bone loss, were reported by few selected studies; they are considered as limitation of this systematic review .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The current results are comparable with previous systematic reviews comparing short implants to longer implants and showed no significant difference of marginal bone loss . Crown height space, splinting of crowns, occlusal loading, and implant design that can influence the marginal bone loss, were reported by few selected studies; they are considered as limitation of this systematic review .…”
Section: Discussionsupporting
confidence: 85%
“…The current results are comparable with previous systematic reviews comparing short implants to longer implants and showed no significant difference of marginal bone loss . Crown height space, splinting of crowns, occlusal loading, and implant design that can influence the marginal bone loss, were reported by few selected studies; they are considered as limitation of this systematic review . The uniqueness of the present study was that comprehensive data of short and standard implants were assessed in nine subsets (SH vs ST, SH vs baseline, ST vs baseline, both jaws, maxilla, mandible, up to 1 year, 2‐4 years, 5 years) and tree subgroups (bone type, implant length, and quality of study).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Newly published systematic reviews and meta-analysis have revealed high survival rates of suprastructures and implants after prosthetic rehabilitation with short implants compared with various bone augmentation techniques and placement of standard length implants, which is in accordance with the result of the present systematic review [ 20 , 21 , 41 ]. However, the use of short implants is still considered controversial as a consequence of an unfavourable crown-to-implant ratio, increased risk of biological and technical complications due to potential overload and early implant failure owing to diminished bone-to-implant contact and PIMBL [ 12 , 18 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 90%
“…The disadvantages of bone augmentation (morbidity at the donor site, increased complication risks, increased time and costs, resorption of bone graft etc.) together with the increasing performance of reduced size implants should be kept in mind when developing the treatment plan [23][24][25]. Also, when the ridge is narrow in its coronal part, it is advised to reduce the bone height and insert shorter implants with an increased diameter than longer, narrow implants [26].…”
Section: Discussionmentioning
confidence: 99%